Clarifying the Extraterritorial Application of the European Convention on Human Rights (Al-Skeini v the United Kingdom) - Ryngaert, Cedric (Utrecht Journal of International and European Law, 2012)
In Al-Skeini v the United Kingdom, the European Court on Human Rights clarified the scope ratione loci of the European Convention on Human Rights. Without fully abandoning the territorial concept of jurisdiction, which it had affirmed in the 2001 Bankovic decision, the Court inched somewhat closer to the personal model of jurisdiction. After Al-Skeini, an ECHR Contracting State's exercise of public powers over a given territory, even in the absence of full effective control, may bring persons present in that territory within the State's jurisdiction. The Court did not, however, pronounce itself on the applicability of the ECHR in case (agents of ) a Contracting State exercise governmental authority over persons abroad without exercising public powers over the territory where these persons are located.